Cooperative Maxim Used In The Meaning Of Happy Album By Same-Same - Eka Susylowati (JELLE : Journal Of English Literature, Linguistics, and Education, 2021)
AbstractThe study aims to describe of cooperative maxim in the meaning of happy album by Same-Same song. The research is qualitative study which analyzes the lyrics of song. The data are the lyric of song in the meaning of happy that contains cooperative maxim. The writer collects the data by reading the song lyrics by putting sign and classified cooperative maxim. The result shows that the song  using maxim of relevance and maxim of manner.Keywords: cooperative maxim, lyrics, pragmatics  Abstrak Penelitian ini bertujuan untuk mendeskripsikan maksim kerja sama dalam lagu the meaning of happy album oleh  Same-Same.  Penelitian ini merupakan kualitatif dengan menganalisis lirik lagu The meaning happy oleh Same-Same yang mengandung maksim kerja sama. Pengumpulan data dilakukan dengn mengklasifikasikan lirik lagu yang mengandung makim kerja sama. Hasil penelitian menunjukkan bahwa dalam lagu tersebut menggunakan maksim hubungan dan maksim cara. Kata kunci: maksim kerja sama, lirik, pragmatik